(untitled) (Global Journal of Management and Business Research, 2016)
The main objective of this study is to ascertain the socio-economic determinants of income poverty in rural areas of Ethiopia. A Simple random sampling was used to select 217 household heads from two rural areas Dodola district, Oromia Regional State, in a year 2012. The Binary logistic method was used to find out the determinants of income poverty. The result reveals that determinants of income poverty include household size, number of income sources of the household, livestock and farm land ownership. Poverty status is negatively associated with number of income sources of the household, livestock and farm land ownership. However, family size is positively related to poverty. Finally the study suggests the rural households should diversify their income sources. The households should also be effectively involved in family planning.